COVID-19 cases treated with classical homeopathy: a retrospective analysis of International Academy of Classical Homeopathy database - Seema Mahesh; Petr Hoffmann; Cristiane Kajimura; George Vithoulkas; International Academy of Classical Homeopathy (IACH) (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background The COVID-19 pandemic has posed an unprecedented challenge to global health. Classical homeopathy may have a role to play in alleviating this burden. The objective of this study was to curate data on the treatment effect of classical homeopathy for COVID-19 in a real-world scenario to guide future scientific investigations. # Methods Classical homeopaths from the International Academy of Classical Homeopathy (IACH) were asked to provide details on cases they treated by filling out a standardized questionnaire. COVID-19 cases were defined according to World Health Organization (WHO) criteria as suspected/probable/confirmed cases, with intervention provided being either stand-alone classical homoeopathy or combined with conventional therapy for COVID-19. Cases were followed up with main outcomes being 'improved', 'not improved' or 'progressed' post-treatment. Details of the homeopathic remedies used and main symptoms at the presentation were gathered. Factors associated with main outcomes were investigated with correlational and regression analyses. # Results 367 patients (male 166, female 201) met eligibility criteria (mean age 42.75 years). The mean follow-up period was 6.5 (standard deviation, SD=5.3) days. 255 were confirmed COVID-19 cases, with 61 probable and 51 suspected cases, respectively. The most used remedy was *Arsenicum album*. Over 73% of COVID-19 patients (and about 79% of severe cases) improved under classical homeopathic treatment. The number of remedies required per individual was negatively correlated to improvement (*P*\< 0.01). Fever, the most common symptom at presentation (74.4%), was associated with an increased likelihood of improvement (*P*\<0.01). Improvement was negatively associated with advanced age, but not associated with sex (*P*\<0.01). # Conclusions This study suggests that classical homeopathy was associated with improvement in COVID-19, including severe cases. Despite limitations from study design and data sources, our findings should prompt further studies on the role of classical homeopathy in the management of COVID-19.